2005
DOI: 10.1021/jo0484878
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Acyl Substitutions of Esters with Protic Nucleophiles Mediated by Amphoteric, Oxotitanium, and Vanadyl Species

Abstract: [reaction: see text] A diverse array of oxometallic species were examined as catalysts in nucleophilic acyl substitution (NAS) reactions of methyl (or ethyl) esters with protic nucleophiles. Among them, oxotitanium acetylacetonate (TiO(acac)(2)) and vanadyl chloride (VOCl(2)-(THF)(x)()) served as the most efficient and water-tolerant catalysts. Transesterifications of methyl and/or ethyl esters with functionalized (including acid- or base-sensitive) 1 degrees and 2 degrees alcohols can be carried out chemosele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Transesterification (Scheme 2), reactions producing esters by catalytical alcoholysis of other esters, also play an important role in the industry, for instance in the manufacture of glycerol esters in fat chemistry (e.g., biodiesel), the transesterification of dimethyl carbonate to diethyl carbonate, or the production of polyethylene terephthalate from dimethyl terephthalate. For these reactions, the usual catalysts are Brønsted mineral acids (H 3 PO 4 , H 2 SO 4 , HCl) [24][25][26], and organic acids such as MeSO 3 H and p-toluenesulfonic acid (TsOH) [27], alkoxides such as NaOR, KOR, ROMgBr [28][29][30][31][32], Lewis bases such as 4-dimethylaminopyridine (DMAP) [33,34], 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU) [35], Lewis acids such as BX 3 [36], or AlCl 3 [37], amphoteric Catalysts 2016, 6, 128 5 of 65 compounds (compounds able to react either as acids or bases) such as Bu 3 SnOR [38][39][40][41], perfluorotin oxides [42], Al(OR) 3 [43,44], titanium oxides chlorides [45][46][47][48] or palladium oxides [49,50]. More recently, diaminocarbenes have been introduced as catalysts as well [51][52][53][54].…”
Section: Acyl Group Transfersmentioning
confidence: 99%
See 1 more Smart Citation
“…Transesterification (Scheme 2), reactions producing esters by catalytical alcoholysis of other esters, also play an important role in the industry, for instance in the manufacture of glycerol esters in fat chemistry (e.g., biodiesel), the transesterification of dimethyl carbonate to diethyl carbonate, or the production of polyethylene terephthalate from dimethyl terephthalate. For these reactions, the usual catalysts are Brønsted mineral acids (H 3 PO 4 , H 2 SO 4 , HCl) [24][25][26], and organic acids such as MeSO 3 H and p-toluenesulfonic acid (TsOH) [27], alkoxides such as NaOR, KOR, ROMgBr [28][29][30][31][32], Lewis bases such as 4-dimethylaminopyridine (DMAP) [33,34], 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU) [35], Lewis acids such as BX 3 [36], or AlCl 3 [37], amphoteric Catalysts 2016, 6, 128 5 of 65 compounds (compounds able to react either as acids or bases) such as Bu 3 SnOR [38][39][40][41], perfluorotin oxides [42], Al(OR) 3 [43,44], titanium oxides chlorides [45][46][47][48] or palladium oxides [49,50]. More recently, diaminocarbenes have been introduced as catalysts as well [51][52][53][54].…”
Section: Acyl Group Transfersmentioning
confidence: 99%
“…Other oxometallic species catalyze nucleophilic acyl substitution reactions with protic nucleophiles. Examples are TiO(acetylacetonate) 2 , vanadyl dichloride VOCl 2 (THF) n , [48] and Y 5 (O-i-Pr) 13 O [76], all being water-tolerant catalysts.…”
Section: Catalysis By Nucleofugal Group Substitutionmentioning
confidence: 99%
“…Acyl transfer reactions have been intensively studied due to their great importance both in biological processes and in synthetic applications . Recently, we have kinetically studied the substituent effect in a nonleaving group on the reactivity of 4‐nitrophenyl benzoates with 4‐chlorophenol and with benzenethiol in the presence of potassium carbonate in DMF .…”
Section: Introductionmentioning
confidence: 99%
“…Yamamoto and Ishihara et al reported highly efficient and direct ester condensation in hydrocarbons by using hafnium(IV) salts such as an HfCl 4 ·(THF) 2 catalyst under azeotropic reflux conditions. Transesterification of various esters with alcohols using heterogeneous and homogeneous acidic catalysts has also been reported 28 29 30 31 32 33 34 35 36 37 38 .…”
mentioning
confidence: 96%